Studying the relationship between spiritual intelligence of nurses and patients' satisfaction with nursing care - Fatemeh Merati Fashi (Bali Medical Journal, 2017)
Background: One of the indices for measuring the performance of any organization including hospitals is the satisfaction of their customers. The purpose of satisfying is client judging of the rate of his expectations from services that they had taken. Patients are expected to care taken by individuals that having a mutual understanding. In the major studies role of traits behavioral and intelligence variety of the medical staff is highly significant on the patient satisfaction, including the intelligence is spiritual intelligence that could help the relationship between staffs and patients. Having high intellectual intelligence help to medical staffs to understand their services meaningful and cope better with the pressures of work. Despite numerous studies which did not consider the effect of a variety of the medical staffs’ intelligence on the patients' satisfaction. In line with this lack, the purpose of this paper is to investigate the relationship between the spiritual intelligence of nurses with patients' satisfaction with nursing care. Methods: This was a descriptive-analytical study that evaluates nursing staff and patients admitted to hospitals in Kermanshah. To collect data, spiritual intelligence and patients' satisfaction questionnaire were used. The data were analyzed by software SPSS22, using descriptive statistics (percent, diagram, mean) and Pearson correlation coefficient. Results: the results showed a significant relationship between nurses spiritual intelligence and patient satisfaction(r=.69, p<0.05). 30% of the nurses had average spiritual intelligence, and patients' satisfaction was desirable. The most satisfying was from the area of utility services (66.9%), the satisfaction of nurses (98%), and satisfaction of doctors (93%). The lowest satisfaction is in the field of patient education and receives information (31.53%). Conclusion: There was a meaningful relationship between nurses’ spiritual intelligence and patient satisfaction. Therefore, considering spiritual dimensions in staffs can increase the quality of care and patient satisfaction.